Manolis I. Stefanakis (ed.), Kymissala: Archaeology-Education-Sustainability. - Wallace, Saro (Journal of Greek Archaeology, 2022)
Manolis I. Stefanakis (ed.), Kymissala: Archaeology-Education-Sustainability. pp. xii+192, with 147 col. and b/w ills, plates, and tbls. Oxford: Archaeopress, 2018. ISBN 9781-78491-768-5, paperback £42; open access E-book via Archaeopress website.